Cerebral Embolic Protection and Outcomes of Transcatheter Aortic Valve Replacement: Results From the Transcatheter Valve Therapy Registry. Issue 23 (23rd February 2021) - Butala, Neel M.; Makkar, Raj; Secemsky, Eric A.; Gallup, Dianne; Marquis-Gravel, Guillaume; Kosinski, Andrzej S.; Vemulapalli, Sreekanth; Valle, Javier A.; Bradley, Steven M.; Chakravarty, Tarun; Yeh, Robert W.; Cohen, David J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Stroke remains a devastating complication of transcatheter aortic valve replacement (TAVR), which has persisted despite refinements in technique and increased operator experience. While cerebral embolic protection devices (EPDs) have been developed to mitigate this risk, data regarding their impact on stroke and other outcomes after TAVR are limited. Methods: We performed an observational study using data from the Society for Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry. Patients were included if they underwent elective or urgent transfemoral TAVR between January 2018 and December 2019. The primary outcome was in-hospital stroke. To adjust for confounding, the association between EPD use and clinical outcomes was evaluated using instrumental variable analysis, a technique designed to support causal inference from observational data, with site-level preference for EPD use within the same quarter of the procedure as the instrument. We also performed a propensity score–based secondary analysis using overlap weights. Results: Our analytic sample included 123 186 patients from 599 sites. The use of EPD during TAVR increased over time, reaching 28% of sites and 13% of TAVR procedures by December 2019. There was wide variation in EPD use across hospitals, with 8% of sites performing >50% of TAVR procedures with an EPD and 72% performing no procedures with an EPD in the last quarter of 2019. In our primary analysis using the instrumental variable model, there was no association between EPD use and in-hospital stroke (adjusted relative risk, 0.90 [95% CI, 0.68–1.13]; absolute risk difference, −0.15% [95% CI, −0.49 to 0.20]). However, in our secondary analysis using the propensity score–based model, EPD use was associated with 18% lower odds of in-hospital stroke (adjusted odds ratio, 0.82 [95% CI, 0.69–0.97]; absolute risk difference, −0.28% [95% CI, −0.52 to −0.03]). Results were generally consistent across the secondary end points, as well as subgroup analyses. Conclusions: In this nationally representative observational study, we did not find an association between EPD use for TAVR and in-hospital stroke in our primary instrumental variable analysis, and found only a modestly lower risk of in-hospital stroke in our secondary propensity-weighted analysis. These findings provide a strong basis for large-scale randomized, controlled trials to test whether EPDs provide meaningful clinical benefit for patients undergoing TAVR.